AB0585 The Study on the Uric Acid Level of the Fertile Female Systemic Lupus Erythematosus Patients. (9th June 2015) - Liu, H.-J.; Ma, J.-D.; Mo, Y.-Q.; Zheng, D.-H.; Cai, X.-Y.; Xie, M.-Y.; Dai, L.
Abstract : Background: Whether the fertile female systemic lupus erythematosus (SLE) patients have low incidence of hyperuricemia like healthy fertile women? There were few reports yet. Objectives: To explore the urine acid (UA) level and its influence fators in the fertile female SLE patients. Methods: Fertile female SLE patients were recruited as well as healthy fertile women as control. Blood UA concentration were tested and compared. In the SLE group, patients were further divided into two subgroups (high UA subgroup and normal UA subgroup, by 358 μmol/l), and the kidney index, SLE disease indicators, SLEDAI score and blood lipid level were compared between them. To determine the independent factors affecting the UA level of SLE patients, binary logistic regression analysis and multiple linear regression analysis were further applied. Results: 1.The mean age of the SLE group (n=107) and the control group (n=50) were (28.93±7.98) years and (30.34±5.85) years, with no significant difference (t=-1.142, p<0.05). The median disease duration of the SLE group was (25.64±31.11) months. Only seven SLE patients presented renal failure, and the average CRE level of the SLE group was (87.56±63.26) μmol/l.The average SLEDAI was 7.07±5.86. 2.The mean UA concentration of the SLE group and the control group were (367.43±159.86) μmol/l and (296.78±69.87) μmol/l, with remarkable distinction (t=3.852, P<0.001). The incidence of high UA in the SLE group and the control group were 42.06% and 14%, with significant difference (χ 2 =12.109, P<0.05). 3.16 SLE patients received the medications that may increase the UA level, including azathioprine and cyclosporin. The binary logistic regression analysis indicated that these medications were not the risk factor of high UA in SLE patients (95%CI 0.268–2.389, P>0.05). 4.In the high UA subgroup (n=45) of the SLE group, CRE, TG, LDL and HDL were dramatically higher than those of the normal UA subgroup (n=62, t=2.582, 2.941, -2.691, all P<0.05), and C3 was markedly lower than that of the normal UA subgroup (t=-3.225, P<0.05). The positive rates of anti-dsDNA and urine blood of the high UA subgroup were significantly higher than those of the normal UA subgroup (χ 2 =7.010, 7.489, both P<0.05). 5.The multiple linear regression analysis indicated that CRE, TG, HDL and urine blood were the independent factors for UA level of SLE patients (t=4.383, 3.182, -2.036, 2.692, all P<0.05, table 1 ). Conclusions: The fertile female SLE patients showed higher incidence of hyperuricemia than healthy fertile women, and CRE, TG, HDL and urine blood were the independent factors for UA level. Disclosure of Interest: None declared